2022
DOI: 10.3389/feart.2022.794634
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling Intricacies of Monsoon Attributes in Homogenous Monsoon Regions of India

Abstract: India observes the summer monsoon in June–July–August–September (JJAS) season, and the livelihood security of a huge population depends on it. The impact of the monsoon onset timing, length of monsoon season, rainfall amount, and related extreme events is huge on the Indian economy. Therefore, understanding the inherent intricacies needed a detailed investigation. In five homogenous monsoon regions of India, the trend of monsoon onset and the length of monsoon season are examined. The association between 1) mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 59 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…Therefore, the policy and planningrelated institutions should consider these regions as vulnerable districts, and a highly refined framework must be prepared to mitigate the impacts in the long term. While investigating the intricacies of the monsoon onset, Saini et al (2022) found its relation with the length of the monsoon season and the amount of rainfall [1]. Therefore, in the long term, changing patterns and timing of the monsoon onset can influence the regime of agriculture, disease proliferation, river regime, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the policy and planningrelated institutions should consider these regions as vulnerable districts, and a highly refined framework must be prepared to mitigate the impacts in the long term. While investigating the intricacies of the monsoon onset, Saini et al (2022) found its relation with the length of the monsoon season and the amount of rainfall [1]. Therefore, in the long term, changing patterns and timing of the monsoon onset can influence the regime of agriculture, disease proliferation, river regime, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Monsoon onset is generally viewed with the isochrones passing through different regions, and it has been observed that those isochrones are not dense enough to provide the monsoon onset date at a finer spatial scale [1]. Various methodologies for the determination have been introduced, and in most cases, each one of them uses different criteria [2].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we use 5 different interpolation methods to obtain high-resolution values and compare them. These include Spline (Saini et al, 2022), Kriging (Yang et al, 2014), Inverse Distance Weighted (IDW) (Zhu et al, 2004), Natural Neighbor Interpolation (NNI) (Habib et al, 2021), Bilinear Interpolation (BI) (Meng et al, 2022).…”
Section: Spatial Interpolationmentioning
confidence: 99%
“…The Pearson correlations conducted to compare y r and ten-day sunshine time, ten-day precipitation, and Q s , as shown in Figure 2d,e,f, Figure 3d,e,f, Figure 4d,e,f, Figure 5d,e,f and Figure 6d,e,f, were derived using Origin 2022b software (OriginLab Corporation, Northampton, MA, USA). The extracted event years were determined by the behavior of y r and ten-day sunshine time, ten-day precipitation, and Q s excess the mean value ± 1 standard deviation (hereafter SD) [30], and the results are shown in Tables 1-5. Table 1.…”
Section: Statistical Analysesmentioning
confidence: 99%